A Critical Overview of Systematic Reviews of Shenfu Injection for Heart Failure - Jinke Huang; Yanlu Wang; Suihe Huang; Xiaohui Qin; Fang Yan; Min Shen; Yong Huang (Hindawi-Wiley, 2021)
Objectives. Shenfu Injection (SFI) was widely used in the treatment of heart failure (HF) in China. A plethora of systematic reviews/meta-analyses (SRs/MAs) has been conducted in this research area, although with scattered results. The purpose of this overview was to conduct a comprehensive review to summarize and critically evaluate the existing evidence. Methods. Digital databases were searched for SRs/MAs up to January 28, 2021. Two authors independently screened the reviews and assessed the methodological quality of included SRs/MAs using Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR-2). Quality of evidence for outcomes evaluated within the reviews was appraised with the Grading of Recommendation, Assessment, Development, and Evaluation (GRADE). Results. Thirteen SRs/MAs met the inclusion criteria. Based on AMSTAR-2, the quality of all SRs/MAs was critically low, because all of them have more than one critical domains that were unmet. Based on GRADE, the evidence quality of 24 outcome measures was low or very low, 27 outcome measures was moderate, and none outcome measure was high. Descriptive analysis showed that SFI was an effective and safe method for HF. Conclusions. The use of SFI for the treatment of HF may be clinically effective and safe. However, this conclusion must be interpreted cautiously due to the generally low methodological quality and low evidence quality of the included SRs/MAs. More rigorously designed SRs/MAs and RCTs with high methodological quality are necessary for further proof.